Consideration of a case of malignant melanoma of the vulva - Pacora Castro, Luis (2015)
Messrs. Delegates, I will try to explain in this scientific fair, our modest experience of a particular case of malignant melanoma of the vulva. It is a job with no statistical value communicated by its topographical rarity and better orient its indicated therapeutic. Few cases listed in the literature as those studied by Allen Roy Waldo Miner, Ulfender, etc. In our environment Valdivia found a case in November 1959 and in May 1960 we Frequent menopause age, but usually occurs in adolescence as the hospital studied in Connecticut in 1948. Our case was a mixed patient 43 years of Picnica constitution, shaping and normal development, which showed the characteristic triad of black tumor, located in the external genitalia of an approximate size of 5 x 5 cm .; intermittent intense itching and pain. In the preferred clinical examination found enlarged left inguinal lymph volume two had 4 x 3 cm, approximately.; hard, mobile, non-painful that slid on the underlying levels. In the genital region appreciate a black ulcerated tumor on the top of the left labia majora, stretching from the clitoral region to the upper third of said lip and the skin across the introitus edge to the outer lip root, respecting the meatus urinal. Practice is radical surgery with bilateral inguinal-femoral and pelvic lymphadenectomy, according technique Rupprecht - Bosset, rebound. Tausig first time following the longitudinal incision practice in the sense of femolares vessels to remove the ganglion cell-masses of the groin and femoral node to Cloquet. Then according to Basset, we open the inguinal canal and after exeresis content lymph node entered the round ligament space Bogros and this way took off the bottom of peritoneal bag until the crossroads of the iliac bifurcation where we dissect all greasy squad node to the femoral ring. A finger we remove the obturator lymph of the region and thereby conclude the first operative time. In the second half we practice total vulvectomy, turning in block from the root of the thigh to the vaginal opening, respecting the meatus and one centimeter above the external opening of the anus. The post-operative was superb and after 50 days of hospitalization is discharged back into the Republic. But much to our regret, the patient did not return to the controls suggested ignoring the luck run in the following months. However, we must emphasize that the prognosis nevertheless is bleak given that the iliac lymph were taken.